Effect of the degree of inversion on optical properties of spinel ZnFe2O4. Issue 44 (6th November 2018) - Granone, Luis I.; Ulpe, Anna C.; Robben, Lars; Klimke, Stephen; Jahns, Moritz; Renz, Franz; Gesing, Thorsten M.; Bredow, Thomas; Dillert, Ralf; Bahnemann, Detlef W.
Abstract : The effect of the degree of inversion on the electronic transitions and the Raman scattering of ZnFe2 O4 is revealed. Abstract : Spinel ferrites ( T [M1− x Fe x ] O [M x Fe2− x ]O4 with 0 ≤ x ≤ 1, where M is a bivalent metal ion and the superscripts denote tetrahedral and octahedral sites) are materials commonly used in electronics due to their outstanding magnetic properties. Thus, the effect of the degree of inversion, x, on these properties is well known. However, its effect on other properties of these materials has rarely been investigated in detail. Since ferrites gained much attention during the last decade as visible light active photocatalysts and photoelectrocatalysts, understanding the effect of the degree of inversion on the optical properties became necessary. Among photocatalytically and photoelectrocatalytically active spinel ferrites, zinc ferrite (ZnFe2 O4, ZFO) is one of the most widely studied materials. In this work, five ZFO samples with degrees of inversion varying from 0.07 to 0.20 were prepared by a solid-state reaction employing different annealing temperatures and subsequent quenching. Raman and UV-Vis-NIR spectra were measured and analyzed together with theoretical results obtained from ab initio calculations. Changes in the UV-Vis-NIR spectra associated with electronic transitions of tetrahedrally and octahedrally coordinated Fe 3+ ions are distinguished. However, the optical band gap of the material remains unchanged as the degree of inversion varies. Based on the experimental and theoretical results, a new assignment for the Raman active internal modes and the electronic transitions of ZFO is proposed.